MITIGATING THE POTENTIAL CONSEQUENCES OF CLIMATE CHANGE AND THE GLOBAL WEATHER PATTERNS IN KIM STANLEY ROBINSON’S FIFTY DEGREES BELOW: AN ECO-CONSCIOUS PERSPECTIVE - Rejitha R; S. Vahitha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In his novel Fifty Degrees Below, the second book of his Science in the Capital Trilogy (also titled Green Earth), Kim Stanley Robinson triggers the impact of climate change on Earth and mitigates the upsurging crisis. This paper analyses the crucial efforts that are to be taken to battle anthropogenic climate change which is essentially the human influence of climate change on Earth’s climate patterns. The paper also aims at exposing the palaeolithic lifestyle adopted by the National Science Foundation scientist Frank Vanderval as he practises outdoor sleeping and hunting. Robinson’s plea for scientific approaches to restart the Gulf Stream is reiterated in this article to avert ecological disasters. Robinson’s narrative is framed in its ethical obligation to protect the forthcoming generations from the consequences of climate change. The paper focuses on the rising temperatures juxtaposing the connection of science, politics, and policy-making. The necessity to practice new climatic adaptations is also revealed in the paper to protect the ecological environment as implemented by Robinson. The various strategies to address climate change as implied by Robinson are effectively portrayed in the paper to analyse the global weather patterns from an eco-conscious perspective.